Analysis of the social capital indicators by using DEMATEL approach: the case of Islamic Azad University - Kiakojuri, Davood; Shahaboddin, Shamshirband; Nor Badrul, Anuar; Johari, Abdullah (Springer Netherlands, 2015)
DEMATEL is a comprehensive approach for designing and analyzing structural models which includes cause and effect relationships among complex factors and by using it in social and managerial issues can classify and organize the interactive effects of a large number of factors affecting on a particular issue. This technique is mainly considered for studying the global complex problems and determining the strategic and objective goals of the global issues in order to access the appropriate solutions up to use the judgment and opinion of the experts in scientific, political, and social fields. The advantages of this method compared to the AHP and ANP approaches are that it measures the direct and indirect effects among the factors and base on the diagram’s calculations and according to the cause and effect relationships will rank and analysis the intensive effect of direct and indirect impact of the factors in a qualitative way. This paper, first described the DEMATEL method which is one of the well-known method of group decision-making and its applications are described and then its application in evaluating and prioritizing the social capital indicators is discussed. Finally, the implementation of this method in Islamic Azad University is explained.